Levels of heavy metals in tropical fruits and soils from agricultural crops in Antioquia, Colombia. A probabilistic assessment of health risk associated with their consumption (2025)
ABSTRACT: Heavy metals such as lead (Pb), mercury (Hg), cadmium (Cd), arsenic (As), and chromium (Cr) occur naturally in the environment and can be released through human activities such as mining and industry. These metals can accumulate in the biota and humans, furthermore, posing dangers through the consumption of contaminated foods, including fruits even at low levels. Therefore, the objective of this study was to evaluate the levels of these pollutants in tropical fruits and soils of Antioquia, Colombia. Furthermore, the health risk by consumption was estimated. 56 fruit samples (Hass avocado, cape gooseberry, and purple passion fruit) and 32 soil samples were collected from 8 farms between March 2023 and January 2024. The samples were digested/extracted and analyzed by inductively coupled plasma atomic emission spectrometry assisted by microwave. Levels above the maximum level of Hg (0.01 mg/kg), Pb (0.200 mg/kg), and As (0.500 mg/kg) were found in the three fruits of the study. Hass avocado had the highest Hg concentration (0.367 mg/kg); purple passion fruit had the highest Pb concentration (0.612 mg/kg), and cape gooseberry had the highest As concentration (0.179 mg/kg). Cd and Cr were not detected in fruits. In the soil, the mean levels of Hg and Cd were 3.46 mg/kg and 4.91 mg/kg, respectively. All samples exceeded the regulatory limits for these metals (Hg 0.450 mg/kg and Cd 1.00 mg/kg). The rest of the metals were below the regulatory limit in the soil. Irrigation water (groundwater) was identified as the main source of contamination because plants could uptake metals by roots due to its similarity with essential metals. The Hazard Quotient (HQ) in Hass avocado of Hg and Pb was 1.07 and 1.20; and in purple passion fruit to Pb was 1.28 in the 95th percentile. The above indicated a non-carcinogenic risk by consumption. It is worth noting that the risk was calculated considering the worse scenario for the population, such as high-rate intakes for a long term of exposure and high frequency of intake. Finally, the results indicated a high presence of these metals in fruits, contrary to expectations based on the matrix type. These highlight the need for ongoing monitoring to reduce exposure risks for the local population, as noncarcinogenic risks from Hg and Pb consumption were found. These findings encourage further research on this issue in the country and provide an overview of exposure that could be useful to environmental health policies and protect public health.